FAKTOR PERSEPSI RESPON EFEKTIF BERHUBUNGAN DENGAN NIAT ANGGOTA KEPOLISIAN MELAKUKAN TES HIV DI POLRES MALUKU TENGGARA - Jeane Irene Levy Ratulangi (Poltekkes Kemenkes Maluku, 2017)
There are four factors of perception associated with the intention of members of the police force conducting HIV testing among others perception of effective response. This research aims to know the perception of effective response factors associated with the intention of members of the police force conducting HIV testing in Southeast Maluku Regional Police. Research methods a descriptive analytic design done cross-sectional with quantitative approach. The respondents in this research is a member of the Southeast Maluku Regional Police with 354 men taken in total samples. Data analysis using univariate techniques, bivariate with Chi-Square test and Logistic Regression with multivariate techniques. The results of this research, there is a significant associated between the perception of effective response do HIV testing with the intention of members of the police force do HIV testing. While the most dominant factor is the effective response do HIV testing. From this research it can be concluded that the perception of effective response to do HIV testing can influence the occurrence of police members intentions Southeast Maluku Regional Police to do HIV testing.